Fagodisuasión de extractos vegetales en larvas de Hypsipyla grandella - Mancebo, Fernando; Hilje, Luko; Mora, Gerardo A.; Salazar, Rodolfo (CATIE, Turrialba (Costa Rica), 2020)
5 páginas, ilustrado, 2 figuras, 18 referencias.